Cancer of the anal canal: A radiochemo curable neoplasm - Torres, Miguel; Avondet, Isabel; Vázquez, Javier; Santini, Alejandro (Cirugía del Uruguay, 1997)
This paper makes a thorough revision of this regions anatomy, treatment history and present treatments for cancer of the anal canal.